APPLICATION OF RADIO FREQUENCY IDENTIFICATION INTERNET OF THINGS-BASED ATTENDANCE SYSTEM AT CV VIARTHA MEDIATAMA PRINTING - Pinasthi, Rendra Bayu; Arifin, Rita Wahyuni (Universitas Islam Balitar, 2025)
Along with the rapid advancement in information technology, various industrial sectors have adopted Internet of Things (IoT)-based systems to improve work efficiency. One appropriate application of this technology is in employee attendance systems. The purpose of this study is to design and develop an automatic attendance system that integrates Radio Frequency Identification (RFID) technology with an Arduino microcontroller and an ESP8266-based IoT module at CV. Viartha Mediatama. This system uses RFID cards as employee identification tags, an RC522 RFID reader module to detect card data, an Arduino integrated development environment (IDE) as a controller unit, and an ESP8266 NodeMCU to transmit data to the server in real-time. The received data is stored in a MySQL database and displayed through a web interface that administrators can use to monitor and compile attendance data. The trial results show that, as long as an internet connection is available, the system can detect RFID cards quickly and accurately and transmit data smoothly. The implementation of this system simplifies the attendance process at CV. This increases efficiency, minimizes the potential for data manipulation, and simplifies the attendance reporting process.